Dilema Pendidikan - - Mastuhu (Unisia, 2004)
Education is designed to make people prospered and civilized. Among problems of education in Indonesia is, we hardly find someone or a system which could give people a good example in how someone behave and treat each another. Because, education is not only a study from the elementary school to the university, but the most important thing is how education affect our daily life and also in the life of all people in this nation. Education is not just to break the vicious circle of stupid ness, rather, to teach us how to be brightened and unlighted in the hole of life.